Maldivian Women’s Entrepreneurship: Drivers and Barriers to Sustainable Practice (International Journal of Social Research & Innovation, 2023)
Entrepreneurial activity among women is achieving parity globally with those by men. However, critical factors which enable them to succeed, and barriers to women’s entrepreneurship from a developing world context, often remain unknown and unaddressed. Five successful Maldivian women entrepreneurs participated in the narrative research, using semi-structured interviews, which explored their entrepreneurial journeys from inception to the current situation. Their stories demonstrate women entrepreneurs’ resilience, vision for growth, and willingness to contribute to society through innovation, training, mentoring, and sharing of resources. Lack of effective financial and entrepreneurial exposure, limited awareness of business planning and management, limited government support for women’s entrepreneurship, gender discrimination at multiple levels, and lack of political and technological savviness were barriers to sustainability of their entrepreneurship and for increased impact. These entrepreneurs’ candid conversations can be beneficial to address structural barriers and to develop women entrepreneur-friendly policy and programs. Future research could be to investigate similarities and differences between Maldivian men’s and women’s entrepreneurship skills, qualities, and attributes. Youth perspectives and research on emerging concepts of entrepreneurship is also needed.